2023
DOI: 10.1007/s00018-023-04827-3
|View full text |Cite
|
Sign up to set email alerts
|

Loss of functional peroxisomes leads to increased mitochondrial biogenesis and reduced autophagy that preserve mitochondrial function

Abstract: Peroxisomes are essential for mitochondrial health, as the absence of peroxisomes leads to altered mitochondria. However, it is unclear whether the changes in mitochondria are a function of preserving cellular function or a response to cellular damage caused by the absence of peroxisomes. To address this, we developed conditional hepatocyte-specific Pex16 deficient (Pex16 KO) mice that develop peroxisome loss and subjected them to a low-protein diet to induce metabolic stress. Loss of PEX16 in hepatocytes led … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Mitochondrial–peroxisome interaction plays a relevant role in fatty acid metabolism and in cellular redox homeostasis; a coordinate function of these organelles is required to sustain mitochondrial activity. Studies have shown that peroxisomal protein (PEX5 or PEX16) ablation in mice livers led to mitochondrial dysfunction and fragmentation [ 30 , 31 ]. Moreover, PEX16 knockout mice showed that peroxisomes are required to sustain mitochondrial homeostasis upon metabolic stress induced by a high fat diet [ 31 ].…”
Section: Mitochondrial Network Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial–peroxisome interaction plays a relevant role in fatty acid metabolism and in cellular redox homeostasis; a coordinate function of these organelles is required to sustain mitochondrial activity. Studies have shown that peroxisomal protein (PEX5 or PEX16) ablation in mice livers led to mitochondrial dysfunction and fragmentation [ 30 , 31 ]. Moreover, PEX16 knockout mice showed that peroxisomes are required to sustain mitochondrial homeostasis upon metabolic stress induced by a high fat diet [ 31 ].…”
Section: Mitochondrial Network Architecturementioning
confidence: 99%
“…Studies have shown that peroxisomal protein (PEX5 or PEX16) ablation in mice livers led to mitochondrial dysfunction and fragmentation [ 30 , 31 ]. Moreover, PEX16 knockout mice showed that peroxisomes are required to sustain mitochondrial homeostasis upon metabolic stress induced by a high fat diet [ 31 ]. Two proteins involved in mitochondria–peroxisome tethering have been identified, enoyl-CoA-δ isomerase 2 (ECI2) and the lipid transport protein VPS13D [ 32 , 33 ].…”
Section: Mitochondrial Network Architecturementioning
confidence: 99%